A Postcolonial Study of the Representation of South Asian Immigrants Dwelling Post-imperial London in Hanif Kureishi’s The Buddha of Suburbia - Seba, Noura; Bourahla, Nadjat; Selt, Djihad Afaf (Faculty of Letters and Foreign Languages Department of English, 2023)
The British Empire colonized extensive territories, which has resulted in the emergence of a genre of literature called Black British literature. This genre portrays the experiences of specific communities within the British metropolis. This dissertation aims to explore themes of displacement and cultural dislocation experienced by first and second-generation South Asian immigrants in the novel The Buddha of Suburbia (1991) by Hanif Kureishi. To achieve this goal, this work is carried out using a postcolonial approach following a descriptive method. This dissertation questions various challenges addressed in Black British literature, with a particular focus on the process of assimilation in postcolonial London for immigrants after the decline of the British Empire. Kureishi offers insights into cultural conflicts and sheds light on the encounters between South Asian roots and Western society. This project concludes that the colonial past of post-colonial immigrants hinders their assimilation process. Additionally, Kureishi creates characters that dismantle the traditional notions of identity and represent the complex reality of South Asian immigrants' experiences